Rancang Bangun Sistem Informasi Produksi Terracotta di Perusahaan Gerabah Kabupaten Bantul DIY - Ike Yunia Pasa; Wahju Tjahjo Saputro (Universitas Muhammadiyah Purworejo, 2020)
Terracotta is clay that is processed through several stages until it becomes ceramic handicraft items. Example of terracotta in Kab. Bantul Yogyakarta is located in Kasongan, Kasihan, Bantul. However, in Yogyakarta, there are also several companies engaged in the terracotta sector, which are able to produce independently and then export the results. Currently, the obstacles faced by several terracotta companies in Kab. Bantul Yogyakarta is an irregular and well-administered production data processing process. The main cause is the location or area of ​​the Production Section which is limited and there are no clear dividing boundaries between subsections. Each subsection can claim that the existing data belongs to the relevant subsection. This causes the physical data and data in the administration to be incompatible. Moreover, the process of transferring goods continues even at night. Where in this condition, the transfer of goods may not be recorded properly. To overcome these problems, in this study the constraints in the terracotta company were taken as material in making a prototype application system that is able to process terracotta data well. The result of this research is the realization of an information system to monitor the movement of pottery in the production section. The system can work well even though communication between subsections becomes an obstacle related to the number of pottery stocks produced.